Development of colorimetric cholesterol detection kit using TPU nanofibre/cellulose acetate membrane. Issue 5 (28th February 2018) - Immanuel, Susan; Elakkiya, Venugopal; Alagappan, Muthuppalaniappan; Selvakumar, Rajendran
Abstract : In this study, the authors report a simple fabrication of thermoplastic polyurethane (TPU) nanofibres‐based kit for cholesterol detection. TPU is a polymer that is highly elastic, resistant to microorganisms, abrasion and compatible with blood; thus, making it a natural selection as an immobilisation matrix for cholesterol oxidase (ChOx) enzyme. The nanofibre was fabricated by electrospinning process and was characterised using scanning electron microscopy and Fourier transform‐infrared spectroscopy. ChOx was covalently immobilised on TPU nanofibre and cholesterol level/concentration was visually found using 4‐aminoantipyrine, a dye that reacts with H2 O2 produced from the oxidation of cholesterol by ChOx and changes colour from yellow to red. The efficacy of the nanofibre to act as a detecting substrate was compared with cellulose acetate (CA) membrane, a well‐documented enzyme immobilisation matrix. The optimisation of enzyme concentration and dye quantity were performed using standard ChOx spectrophotometric assay and the same was used in CA membrane and TPU nanofibre. The ChOx immobilised nanofibre showed good linear range from 2 to 10 mM with a lower detection limit of 2 mM and was highly stable compared to that of CA membrane. The enzyme immobilised nanofibre was further validated in serum samples.